Anomalous sublimation passivation of nanotwinned silver particles. Issue 5 (3rd May 2020) - Sun, Yong; Wang, Jinming; Guo, Jianxin; Wang, Jin; Peng, Qiuming
Abstract : Metal sublimation plays a crucial role in understanding natural phenomena, purification and advanced manufacturing. Herein, we report anomalous sublimation passivation of nanotwinned silver particles under e-beam irradiation through in situ transmission electron microscopy, wherein the sublimation velocity is reduced by three-quarters due to the formation of five-fold twins. Theoretical calculations reveal that this sublimation passivation mechanism is mainly related to the increment in sublimation energy by the presence of twin boundaries. GRAPHICAL ABSTRACT: IMPACT STATEMENT: Differing from traditional cognition of defect-assisted sublimation, anomalous sublimation passivation of nanotwinned silver particles under e-beam irradiation has firstly been identified in terms of TEM observations and DFT calculations.